(untitled) (Revista de Biología Marina y Oceanografía, 2024)
Nototheniidae is the most numerous family of notothenioids and, although they are mainly Antarctic, they are also well represented in Patagonian waters. In both Antarctic and sub-Antarctic waters, they adopt a wide variety of reproductive strategies. In Antarctic waters they usually have a biennial reproductive cycle, whereas in sub-Antarctic ones, they reproduce annually or biannually. In the intertidal zone of central Patagonia the most abundant nototheniid fish is Patagonotothen cornucola and, despite this, there is little information about their biology. The aim of this work was to study its reproductive cycle in a rocky intertidal coast of Argentine Patagonia by means of histological and morphological analyses. Samples were collected monthly at two intertidal sites in the San Jorge Gulf. Condition factor, gonadosomatic and hepatosomatic indexes were calculated and thin sections of gonads were stained with one-step trichrome to determine gonadal stages. Relative and potential fecundity were also estimated. Males and females mature synchronously and reach maximum gonadosomatic index between July and August. In females the hepatosomatic index increases synchronously with gonadosomatic index, while in males it remains constant throughout the cycle. It is concluded that P. cornucola has an annual reproductive cycle and that spawning occurs in winter. Maximum potential fecundity is approximately 27,095 oocytes in a 11.7 cm female and it increases with size.